2006
DOI: 10.1111/j.1475-6765.2006.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and the transformation of the national political space: Six European countries compared

Abstract: Abstract. This article starts from the assumption that the current process of globalization or denationalization leads to the formation of a new structural conflict in Western European countries, opposing those who benefit from this process against those who tend to lose in the course of the events. The structural opposition between globalization 'winners' and 'losers' is expected to constitute potentials for political mobilization within national political contexts, the mobilization of which is expected to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
861
7
51

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,175 publications
(987 citation statements)
references
References 48 publications
19
861
7
51
Order By: Relevance
“…This second dataset elaborates on the principles of the 'confrontational' approach to manual content analysis (Pellikaan et al, 2003;Kriesi et al, 2006). Here, the basic coding unit is the individual policy proposal or pledge.…”
Section: Methodsmentioning
confidence: 99%
“…This second dataset elaborates on the principles of the 'confrontational' approach to manual content analysis (Pellikaan et al, 2003;Kriesi et al, 2006). Here, the basic coding unit is the individual policy proposal or pledge.…”
Section: Methodsmentioning
confidence: 99%
“…First, they could support them because they agree with these parties' main ideological messages. It has been shown that when it comes to radical right voting, the effect of someone's socioeconomic position is strongly a function of, or mediated by, attitudes toward immigration (see Ivarsflaten, 2008;Kriesi, Grande, Lachat, Dolezal, & Bornschier, 2008;Kriesi et al, 2006;Van der Brug, Fennema, & Tillie, 2000, 2005. In particular, those who experience economic difficulties are likely to have anti-immigration attitudes and in turn, and therefore, vote for a radical right party.…”
Section: Radical Parties and Radical Votingmentioning
confidence: 99%
“…We test our expectations in Western Europe as this allows us to examine wedge issue competition within a set of stable and democratic multiparty systems over three decades. The literature on Western European party competition has identified several issues that constitute wedge issues, such as European integration and immigration (see Green-Pedersen and Krogstup 2008;Kriesi et al 2006;Marks and Wilson 2000;Meguid 2005;Taggart 1998). Ideally, we would test our hypotheses by looking at more than a single wedge issue.…”
Section: The Eu As a Wedge Issuementioning
confidence: 99%